B- mode ultrasound- guided balloon angioplasty of occluded artery accompanied by combined focused ultrasound sonodynamic therapy and catheter- based 192Ir- mediated brachytherapy. (14th October 2021) - Mehrad, H
Abstract: Background and aims: Three mechanisms are responsible for the development of restenosis: elastic recoil, intimal hyperplasia and late vascular constriction, all grouped under the catch phrase "negative remodeling". Neointimal hyperplasia is usually defined in an artery as thickening of the intimal layer after an injury such as balloon angioplasty methods. The aim of this study was to evaluate the effect of combined ultrasound sonodynamic therapy and catheter- based 192Ir-mediated β-brachytherapy on restenosis reduction after balloon angioplasty. Methods: Briefly, golden Syrian hamsters were submitted to common carotid artery advanced atherosclerotic occlusion by primary perivascular Co2 laser-mediated far-infrared injury followed by a 2% cholesterol-rich diet for six weeks. Histopathology results showed the formation of a thick-cap fibroatheromatic plaque, resulted to occlusion in all of the hamsters' arteries. Then treatment group (n=10) underwent B-mode ultrasound-guided balloon angioplasty followed by combined pulsed low level focused ultrasound (F=750 KHz, I=1.5 W/cm 2, PD=120 ms)-mediated sonosensitizer protoporphyrin-IX-loaded PESDA (Perfluorocarbon Exposed Sonicated Dextrose Albumin) microbubbles (100ml/kg, 2–5×10 5 bubbles/ml) sonodynamic therapy and catheter- based β-brachytherapy (125I−, 18 Gy). Results: Results from ultrasonography and histopathology showed a significant reduction in the mean value for macrophages and smooth muscle hyperplasia cells density after balloon angioplasty in the treated group compared with the other groups (p<0.05). Conclusions: Enhanced anti-inflammatory effect of sonodynamic therapy, induced by collapsed microbubbles accompanied by apoptotic effect of β-brachytherapy, can cause to reduce the inflammation and smooth muscle hyperplasia cells in the intimal layer. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Mehrad Research Lab